Synthesis of copper complex and application of copper complex as fluorescent probe and photodegradation catalyst

A copper complex [Cu(BMIOPE)(1,4-NDC)] is used as a fluorescent probe for antibiotic detection and photodegradation catalyst, addressing the inefficiencies of existing methods by enabling rapid and cost-effective detection and treatment of antibiotics and dye wastewater.

CN119176822APending Publication Date: 2024-12-24YANCHENG TEACHERS UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411340119.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing methods for detecting antibiotics like nitrofurantoin and dichromate ions are expensive, complex, and time-consuming, while dye wastewater treatment is inefficient and environmentally harmful.

Method used

A copper complex [Cu(BMIOPE)(1,4-NDC)] is synthesized to serve as a fluorescent probe for detecting nitrofurantoin and dichromate ions and as a photodegradation catalyst for degrading methylene blue dye wastewater, utilizing a simple synthesis method with MOFs materials.

Benefits of technology

The copper complex provides rapid, sensitive, and quantitative detection of antibiotics and dichromate ions, and effectively degrades methylene blue dye wastewater under visible light, with high yield and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176822A_ABST
    Figure CN119176822A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of antibiotic detection, anion detection and dye degradation, and relates to a copper complex as well as preparation and application thereof. The chemical formula of the complex is [Cu (BMIOPE) (1, 4-NDC)], BMIOPE is 4, 4 '-di (2-methyl-1-imidazolyl) diphenyl ether, and 1, 4-H2NDC is 1, 4-naphthalic acid. The complex disclosed by the invention has a fluorescence recognition function on nitrofurantoin, furacilin and dichromate ions, can be used for detecting trace nitrofurantoin, furacilin and dichromate ions in an aqueous solution, and has quenching constants of 8.07 * 10 < 3 >, 7.85 * 10 < 3 > and 6.47 * 10 < 3 > respectively. And the degradation rate of the copper complex disclosed by the invention on methylene blue within 60 minutes is 93.7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibiotic detection, anion detection and dye degradation, and specifically relates to the preparation of a copper complex and its application in the detection of nitrofurantoin (NFT), nitrofurazone (NZF), dichromate ion (Cr2O7 2- ) and application in degradation of methylene blue (MB) dye wastewater. Background Art

[0002] Antibiotics are a class of secondary metabolites produced by microorganisms that have antipathogenic or other therapeutic activities for bacterial infections. Antibiotics mainly include penicillins, tetracyclines and cephalosporins. Antibiotics can inhibit or kill bacteria that are usually transmitted by microorganisms in food, water or the environment, thereby treating infections. However, antibiotics are not omnipotent, and improper or long-term use can lead to the emergence of drug-resistant bacteria. Resistant bacteria can become resistant to existing antibiotics, leading to worsening of the disease.

[0003] Traditional methods for detecting antibiotics mainly include high performance liquid chromatography, thin layer chromatography, and capillary electrophoresis. These traditional methods either require expensive equipment and complex techniques, or involve multiple sample operations and time consumption. Therefore, it is very important to establish a sensitive, rapid, efficient, reliable, and quantitative method for detecting antibiotic concentration.

[0004] Dichromate is an important chemical substance that plays a very important role in our lives. First of all, it can be used to make dyes, coatings, cellulose, etc. Secondly, it can also be used to make antibacterial agents, antioxidants, heat-resistant agents, antiviral agents, etc. Its harm is also very great. With the rapid development of industrialization, the pollution of industrial wastewater to the environment is becoming more and more serious. In industrial wastewater, dichromate ions are the most common and one of the most toxic substances. Dichromate ions can cause heavy metal pollution to the soil, affecting the growth and development of plant roots and the conduct of photosynthesis. At the same time, these heavy metals will also be transferred to animals and humans through the food chain. Dichromate has a strong oxidizing effect and can invade the human body through the skin, respiratory tract, digestive tract, etc., causing inflammation and even cancer in the human body. Therefore, it has been listed as a "Class A" human carcinogen. Therefore, it is very important to detect dichromate ions in water efficiently and accurately, not only for protecting the environment, but also for protecting human health.

[0005] Treatment of dye wastewater has become a prominent environmental protection issue in countries around the world. Dye wastewater has many characteristics, such as high chroma, complex chemical composition, high toxicity, large fluctuations in water quality, and poor biodegradability. The hazards of dye wastewater are mainly manifested in two aspects: one is the harm to the ecological environment; the other is the harm to human health. In recent years, chemists have been committed to finding efficient, environmentally friendly and economical methods to treat dye wastewater.

[0006] MOFs materials, also known as metal organic framework materials, are a type of metal organic material that has developed rapidly in recent years. They are nanocrystalline structured materials. They have the characteristics of large specific surface area, easy functionalization, diverse types, and controllable structure. They have great application potential in gas storage adsorption, optoelectronics, biomedicine, etc. MOFs materials have high thermal and chemical stability and can maintain adsorption at higher temperatures. Therefore, they can be used as fluorescent probes to quickly, effectively, and accurately detect antibiotics and dichromate ions in aqueous solutions. MOFs materials have the characteristics of strong adsorption capacity, high porosity, adjustable structure, and exposed active sites, making them promising to become efficient photodegradation catalysts for dye wastewater treatment. In addition, MOFs materials have the advantages of low cost, simple preparation, adjustable, controllable, and reusable. They have broad application prospects in environmental monitoring, medical diagnosis, degradation, and other fields. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art, and to provide a method for synthesizing a copper complex and its application as a fluorescent probe in detecting nitrofurantoin, nitrofurazone and dichromate ions and as a photodegradation catalyst in degrading methylene blue dye wastewater.

[0008] The chemical formula of the copper complex involved in the present invention that can simultaneously detect nitrofurantoin, nitrofuran and dichromate ions and degrade methylene blue dye wastewater is: [Cu(BMIOPE)(1,4-NDC)], wherein BMIOPE=4,4′-di(2-methyl-1-imidazolyl)diphenyl ether, 1,4-H2NDC=1,4-naphthalene dicarboxylic acid. The structural formula of BMIOPE, 1,4-H2NDC is as follows:

[0009]

[0010] Furthermore, the structural formula of the copper complex is:

[0011]

[0012] The basic structural parameters of the copper complex involved in the present invention that can detect nitrofurantoin, nitrofuran, dichromate ions and degrade methylene blue dye wastewater are as follows: the crystal of the copper complex of the present invention belongs to the orthorhombic system, its space group is Pna21, and the unit cell parameter is α=90°, β=90°, γ=90°, The smallest asymmetric unit of the copper complex consists of a copper ion, a 1,4-NDC 2- anion and a BMIOPE ligand. Each copper ion and two different 1,4-NDC 2- The three oxygen atoms of the ligand are coordinated with the two nitrogen atoms of two different BMIOPE ligands to form a CuO3N2 tetrahedral geometry ( Figure 1 ). Adjacent copper ions pass through 1,4-NDC 2- The ligands are connected to form a one-dimensional [Cu(1,4-NDC)] chain. At the same time, adjacent copper ions are connected through BMIOPE ligands to form a one-dimensional [Cu(BMIOPE)] chain. Finally, adjacent [Cu(1,4-NDC)] and [Cu(BMIOPE)] chains are connected to each other to form a two-dimensional [Cu(BMIOPE)(1,4-NDC)] planar structure ( Figure 2 ).

[0013] The preparation method of the copper complex involved in the present invention comprises the following steps:

[0014] (1) 1,4-naphthalene dicarboxylic acid (0.05 mmol), 4,4′-di(2-methyl-1-imidazolyl)biphenyl ether (0.05 mmol), and copper nitrate hexahydrate (0.05 mmol) were added to a mixed solvent of water (2 ml) and N,N-dimethylformamide (DMA, 0.5 ml) at a molar ratio of 1:1:1, and ultrasonically vibrated for 5 minutes to uniformly disperse the mixture. The mixture was transferred into a 10 ml polytetrafluoroethylene liner, and the 10 ml polytetrafluoroethylene liner was transferred into a 50 ml reactor;

[0015] (2) heating the reactor of step (1) from room temperature to 100° C. within two hours and conducting a constant temperature reaction under autogenous pressure for 72 hours, cooling the product to 40° C. within 30 hours after the reaction, and finally cooling to room temperature;

[0016] (3) The solid separated in step (2) was washed three times with ethanol to obtain blue block crystals, namely the copper complex, with a yield of about 87.1%.

[0017] Furthermore, the present invention provides the use of the above copper complex as a fluorescent probe for nitrofurantoin, nitrofurazone and dichromate ions, which can be used to monitor nitrofurantoin, nitrofurazone and dichromate ions in the environment and organisms at the same time; the present invention provides the use of the above copper complex as a photodegradation catalyst, which can degrade methylene blue dye wastewater.

[0018] The invention has the advantages of simple synthesis method, easy availability of synthetic raw materials, low cost, high synthesis yield and easy industrial production; the product exhibits good fluorescence recognition function for nitrofurantoin, nitrofurazone and dichromate ions, can be used for detecting trace amounts of nitrofurantoin, nitrofurazone and dichromate ions in aqueous solution, and compared with the traditional detection method, the method has the advantages of quantitative, rapid, sensitive, efficient, easy to operate and the like; the product can effectively catalyze and degrade methylene blue dye wastewater under visible light, and the methylene blue dye is basically completely degraded within 60 minutes.

[0019] Figure content

[0020] Figure 1 Figure 2 is a diagram of the copper ion coordination environment of the copper complex of the present invention.

[0021] Figure 2 It is a two-dimensional structure diagram of the copper complex of the present invention.

[0022] Figure 3 The figure is the powder XRD pattern of the copper complex of the present invention.

[0023] Figure 4 It is the thermogravimetric diagram of the copper complex of the present invention.

[0024] Figure 5 It is the solid fluorescence image of the copper complex of the present invention.

[0025] Figure 6 The graph is a fluorescence intensity graph of the copper complex of the present invention in aqueous solutions of nitrofurantoin at different concentrations.

[0026] Figure 7 It is a linear fitting spectrum of the fluorescence peak ratio of the copper complex of the present invention and the concentration of nitrofurantoin.

[0027] Figure 8 The graph is a fluorescence intensity graph of the copper complex of the present invention in aqueous solutions of furacilin at different concentrations.

[0028] Fig. 9 It is a linear fitting spectrum of the fluorescence peak ratio of the copper complex of the present invention and the concentration of furacilin.

[0029] Fig.10 The graph is a fluorescence intensity graph of the copper complex of the present invention in aqueous dichromate ion solutions with different concentrations.

[0030] Fig.11It is a linear fitting spectrum of the fluorescence peak ratio of the copper complex of the present invention and the dichromate ion concentration.

[0031] Fig.12 This is a diagram showing the photocatalytic degradation of methylene blue by the copper complex of the present invention.

[0032] Fig.13 It is the infrared spectrum of the copper complex of the present invention. DETAILED DESCRIPTION

[0033] In order to better understand the present invention, the content of the present invention is further described below in conjunction with implementation examples, but the content of the present invention is not limited to the following embodiments.

[0034] Example 1: Synthesis of complex

[0035] (1) 1,4-naphthalene dicarboxylic acid (0.05 mmol), 4,4′-di(2-methyl-1-imidazolyl)biphenyl ether (0.05 mmol) and copper nitrate hexahydrate (0.05 mmol) were added to a mixed solution of water (2 ml) and N,N-dimethylformamide (DMA, 0.5 ml) in a molar ratio of 1:1:1, and ultrasonically vibrated for 5 minutes to obtain a uniform mixed solution. The mixed solution was then transferred to a 10 ml polytetrafluoroethylene liner, and the 10 ml polytetrafluoroethylene liner was transferred to a 50 ml reactor;

[0036] (2) heating the reactor of step (1) from room temperature to 100° C. within two hours and conducting a constant temperature reaction under autogenous pressure for 72 hours, cooling the product to 40° C. within 30 hours after the reaction, and finally cooling to room temperature;

[0037] (3) The solid separated in step (2) was washed three times with ethanol to obtain blue block crystals, namely the copper complex, with a yield of about 87.1%.

[0038] Experimental Example 1: Crystal structure determination

[0039] Select crystals of suitable quality and size and place them on a Bruker-AXS SMART CCD X-single crystal instrument. The crystal data is scanned with monochromatic purified Mo-Ka rays (graphite monochromator, ), collect the diffraction data of the crystal, restore the diffraction data with S4INT software, and perform absorption correction with SADABS program. The crystal structure was solved by SHELXTL software using the direct method, and the coordinates of all non-hydrogen atoms were determined by the least squares method. The isotropic temperature factor and the anisotropic temperature factor were refined until convergence. The hydrogen atom positions were obtained by the theoretical hydrogenation method, and the crystal structure was refined by the least squares method.

[0040] The copper complex synthesized in Example 1 crystallizes in the orthorhombic system, its space group is Pna21, and the unit cell parameters are α=90°, β=90°, γ=90°, The smallest asymmetric unit of the copper complex consists of a copper ion, a 1,4-NDC 2- anion and a BMIOPE ligand. Each copper ion and two different 1,4-NDC 2- The three oxygen atoms of the ligand are coordinated with the two nitrogen atoms of two different BMIOPE ligands to form a CuO3N2 tetrahedral geometry ( Figure 1 ). Adjacent copper ions pass through 1,4-NDC 2- The ligands are connected to form a one-dimensional [Cu(1,4-NDC)] chain. At the same time, the adjacent copper ions are connected through the BMIOPE ligand to form a one-dimensional [Cu(BMIOPE)] chain. Finally, the adjacent [Cu(1,4-NDC)] and [Cu(BMIOPE)] chains are connected to each other to form a two-dimensional [Cu(BMIOPE)(1,4-NDC)] planar structure ( Figure 2 ).

[0041] Experimental Example 2: Powder XRD

[0042] The powder X-ray diffraction of the copper complex synthesized in Example 1 is basically consistent with the theoretical diffraction peaks simulated by single crystal data, indicating that the prepared copper complex crystals have a high phase purity. Figure 3 shown.

[0043] Experimental Example 3: Thermogravimetric Analysis

[0044] In order to study the stability of the complex, we performed thermogravimetric analysis on the copper complex synthesized in Example 1. Figure 4 The copper complex synthesized in Example 1 experienced significant weight loss in the range of 40 to 360°C, which was mainly due to the decomposition of 1,4-naphthalenedicarboxylic acid and 4,4′-di(2-methyl-1-imidazolyl)biphenyl ether. The residual substance was mainly copper oxide, with an experimental value of 13.87% and a calculated value of 13.39%.

[0045] Experimental Example 4: Solid Fluorescence Properties

[0046] The solid fluorescence properties of the copper complex synthesized in Example 1 were tested using a fluorescence spectrometer, and the results were Figure 5 The solid fluorescence diagram shown shows that the excitation peak of the copper complex is 246 nanometers, and the emission peak is 424 nanometers.

[0047] Experimental Example 5: Detection of Nitrofurantoin Concentration

[0048] By measuring the fluorescence spectrum of the copper complex synthesized in Example 1 in aqueous solutions of nitrofurantoin at different concentrations, the following was obtained: Figure 6 As shown in the fluorescence emission spectrum, it can be seen that the fluorescence intensity gradually decreases with the increase of furantoin concentration, showing an obvious fluorescence quenching effect, indicating that the copper complex can detect the concentration of furantoin in aqueous solution.

[0049] Using the Stern-Volmer equation (I0 / I=1+K sv [M]) calculated the relationship between the relative change ratio of fluorescence intensity (I0 / I) and the concentration of nitrofurantoin, and plotted Figure 7 The SV graph shown shows that the two are linearly related in the low concentration range, and the quenching constant K sV 8.07×10 3 .

[0050] Experimental Example 6: Detection of Furacilin Concentration

[0051] By measuring the fluorescence spectra of the copper complex synthesized in Example 1 in aqueous solutions of furacilin at different concentrations, the following results were obtained: Figure 8 As shown in the fluorescence emission spectrum, it can be seen that the fluorescence intensity gradually decreases with the increase of furacilin concentration, showing an obvious fluorescence quenching effect, indicating that the copper complex can detect the concentration of furacilin in aqueous solution.

[0052] The relationship between the relative change ratio of fluorescence intensity (I0 / I) and the concentration of furazolidone was calculated using the Stern-Volmer equation, and the Fig. 9 The SV graph shown shows that the two are linearly related in the low concentration range, and the quenching constant K sv 7.85×10 3 .

[0053] Experimental Example 7: Detection of dichromate ion concentration

[0054] By measuring the fluorescence spectra of the copper complex synthesized in Example 1 in aqueous dichromate ion solutions of different concentrations, we can obtain Fig.10 From the fluorescence emission spectrum shown, it can be seen that the fluorescence intensity gradually decreases with the increase of dichromate ion concentration, showing an obvious fluorescence quenching effect, indicating that the copper complex can detect the dichromate ion concentration in aqueous solution.

[0055] The relationship between the relative change ratio of fluorescence intensity (I0 / I) and the concentration of dichromate ions was calculated using the Stern-Volmer equation and plotted. Fig.11 The SV graph shown shows that the two are linearly related in the low concentration range, and the quenching constant K sv is 6.47×10 3 .

[0056] Experimental Example 8: Photodegradation of methylene blue dye wastewater

[0057] 30 mg of the copper complex synthesized in Example 1 was weighed and added to 50 ml of a methylene blue aqueous solution (10 mg / L), and then 5 μl of hydrogen peroxide was added. The mixture was stirred in the dark for 30 minutes to allow the copper complex surface to reach adsorption-desorption equilibrium, and then irradiated with a visible light while stirring, with an intensity of 300 watts, a temperature of room temperature, and a pH of about 7. 1 ml of the methylene blue aqueous solution was taken every 10 minutes, and the absorbance change was immediately tested. The photodegradation results showed that the degradation rate of the complex for methylene blue in 60 minutes was 93.7% (as shown in Figure 2). Fig.12 ).

Claims

1. A copper complex capable of simultaneously detecting nitrofurantoin, nitrofurazone and dichromate anions and degrading methylene blue, characterized in that: Its chemical formula is [Cu(BMIOPE)(1,4-NDC)], wherein BMIOPE=4,4′-di(2-methyl-1-imidazolyl)biphenyl ether, 1,4-H2NDC=1,4-naphthalenedicarboxylic acid; the copper complex belongs to the orthorhombic system, its space group is Pna21, and the unit cell parameters are a=90°, β=90°, γ=90°, The smallest asymmetric unit of the copper complex contains a copper ion, a 1,4-NDC 2- anion and a BMIOPE ligand; each copper ion and two different 1,4-NDC 2- The three oxygen atoms of the ligand are coordinated with the two nitrogen atoms of two different BMIOPE ligands to form a CuO3N2 tetrahedral geometry; the adjacent copper ions are connected by 1,4-NDC 2- The ligands are connected to form a one-dimensional [Cu(1,4-NDC)] chain, adjacent copper ions are connected through BMIOPE ligands to form a one-dimensional [Cu(BMIOPE)] chain, and adjacent [Cu(1,4-NDC)] and [Cu(BMIOPE)] chains are interconnected to form a two-dimensional [Cu(BMIOPE)(1,4-NDC)] planar structure.

2. The method for preparing the copper complex according to claim 1, characterized in that: The steps are as follows: under sealed conditions, 1,4-naphthalene dicarboxylic acid, 4,4'-di(2-methyl-1-imidazolyl)biphenyl ether and copper nitrate hexahydrate are mixed, and a copper complex is obtained through a solvent thermal reaction in a mixed solution of water and N,N-dimethylformamide; wherein: the molar ratio of 1,4-naphthalene dicarboxylic acid, 4,4'-di(2-methyl-1-imidazolyl)biphenyl ether and copper nitrate hexahydrate is 1:1:1, and every 0.05 millimole of copper nitrate hexahydrate corresponds to 2.0 milliliters of water and 0.5 milliliters of N,N-dimethylformamide, and the solvent thermal reaction conditions are at 100° C. and the reaction time is three days.

3. Use of the copper complex as claimed in claim 1 or the copper complex prepared by the method as claimed in claim 2 as a fluorescent probe in the field of detecting nitrofurantoin, detecting nitrofurazone, and detecting dichromate ions.

4. A use according to claim 3, characterized in that: The linear fitting curve equation of the relative change ratio of the fluorescence intensity of the copper complex and the concentration of nitrofurantoin (NFT) is: I0 / I=8070[NFT]+1.0059; the linear fitting curve equation of the relative change ratio of the fluorescence intensity of the copper complex and the concentration of nitrofurantoin (NZF) is: I0 / I=7850[NZF]+1.0035; the linear fitting curve equation of the relative change ratio of the fluorescence intensity of the copper complex and the concentration of dichromate ion (Cr2O7 2- ) concentration is: I0 / I=6470[Cr2O7 2- ]+0.9956.

5. Use of the copper complex as claimed in claim 1 or the copper complex prepared by the method as claimed in claim 2 in the field of photocatalytic degradation of dye molecules.

6. The use according to claim 5, characterized in that: The dye molecule is methylene blue; the degradation rate of the complex on methylene blue is 93.7% in 60 minutes.